Effects of Dextromethorphan on Depressive-and Cognitive-Associated Behaviors: A Sexually Dimorphic Study - Ijomone, Omamuyovwi Meashack (Basic Clin Neurosci, 2019)
INTRODUCTION: We investigated the sexually dimorphic effects of Dextromethorphan (DM) on cognitive and depression-like behaviors as well as on hippocampal histology in rats following acute administration. METHODS: Wistar rats of both sexes were treated with 25 or 50 mg/kg of DM for 7 days via intraperitoneal injection. At the end of the administration, behavioral studies were performed on the Tail Suspension Test (TST) for depressive-like behaviors and the Y-maze for cognitive behaviors. The rats’ brains were excised and processed for routine histological analysis. RESULTS: Our results showed that DM significantly increased (P<0.05) immobility time in the TST in male rats but not female ones, and decreased percentage alternation (P<0.001) on the Y-maze in both male and female rats. Histological analysis revealed no morphological changes in the hippocampus following DM treatment. CONCLUSION: DM impairs cognitive functions in both male and female rats without histologic defects in the hippocampus. However, the induced depressive-like behaviors following DM administration may be sexually dependent.